KINERJA BIDANG BINA MARGA PADA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KOTA PEKANBARU - Rani, Delvita; As’ari, Hasim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The performance of Public Works Service and Spatial Planning Pekanbaru City still not as expected, especially of the Bina Marga Field which is charge of optimize development and maintenance of road and bride infrastructure. This can be seen there are still many damaged roads and need repairs. Purpose of this research to knowing of the performance Bina Marga field and what the obstacle factors performance of the Bina Marga Field. This research use theory from Agus Dwiyanto, with five performance assessment indicators, that is productivity, service quality, responsivity, responsibility, and accountability. This research use qualitative research method with explorative research type with file collection techniques through observation, interviews, and documentation. This selection of research informants using purposive sampling technique. The result of this study indicate that there are the performance of Bina Marga Field in the Public Works Service and Spatial Planning Pekanbaru Citystill not as expected andobstacle factors of performance Bina Marga Field Public Works Service and Spatial planning Pekanbaru City, that is budget, human recouces, favilities and infrastructure.Keywords: Performance, road damage